Statistical modelling of awareness on risk factors of gastric cancer: a study on youngsters in Melaka / Izni Syamsina Saari ... [et al.] - Saari, Izni Syamsina; Kedin, Nor Adila; Ab Hamid, Ainon Syazana; Mohd Amirul, Atan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2019)
In Malaysia, gastric cancer (also known as stomach cancer) is diagnosed at a complex stage and has poor prognosis. Most mortality cases due to gastric cancer diseases are potentially preventable. Thus greater efforts are needed for gastric cancer awareness to give adequate knowledge for Malaysians in order to be more cautious or alert in diagnosing the ailment much earlier. After all, early detection is the key towards improving the survival rate in gastric cancer patients. Hence, the aim of this study is to assess the youngsters’ awareness on the risk factors of gastric cancer. A survey using online forms was conducted on 350 students of UiTM Melaka, Alor Gajah Campus, to assess their awareness of risk factors regarding gastric cancer. Based on the regression analysis conducted, it can be highlighted that attitudes, knowledge, medication, education level and faculty (dummy) are some of the variables that were found to be the risk factors of the awareness on gastric cancer among these selected youngsters in the 21st century.